Overview of Self-Management in Hypertension Patients in the Working Area of Sidomulyo Samarinda Health Centre - Fanny Metungku; Mayusef Sukmana; Khumaidi; Nanda Muliadi (Mulawarman Nursing Indonesia Journal, 2023)
Background: Hypertension or high blood pressure that many people know can cause death without complaints and is so dangerous that it gets the nickname "the silent killer", Individuals affected by hypertension can be managed if treated appropriately. One way to manage blood pressure is with good self-management. Objective: This study aims to identify the description of Self Management in Hypertension patients in the working area of Sidomulyo Samarinda health centre. Methods: The method used is a survey method with a quantitative approach. Using consecutive sampling technique as many as 100 respondents in the Samarinda Sidomulyo Health Centre Working Area. The measuring instrument used in measuring knowledge is the Hypertension Self Management Behaviour Quetionnaire (HSMBQ). Results: The results of the study regarding the description of Self Management in Hypertension Patients showed that most respondents had sufficient Self Management as many as 85 respondents (85.0%) greater than respondents who had good Self Management as many as 11 respondents (11.0%) and respondents who had poor Self Management as many as 4 respondents (4.0%). Conclusion: most respondents have sufficient Self Management due to hypertensive patients who rarely do physical activity with the majority of female respondents who work as housewives.